Penegakan Diagnosis dan Penatalaksanaan Retinopati Hipertensi - Maria Devi; Putu Ristyaning Ayu Sangging; Rani Himayani (CV. Jasa Sukses Abadi, 2023)
Hypertension is a global health problem that requires good management. Hypertension is also commonly known as silent killer because it often arises in patients without any symptoms or complaints. There are several factors that affect the prevalence of hypertension such as race, age, obesity, high salt intake, and a history of hypertension in the family. The World Health Organization (WHO) states that in 2019 the prevalence of world hypertension sufferers is 22% of the total world population, and more than four thirds of those with hypertension do not make attempts to control blood pressure that causes hypertension complications. Blood vessels and the retina are highly suggestible structures when a patient suffers from hypertension, one of the target organs of complications of hypertension is the eye, prolonged and uncontrollable hypertension can trigger sclerosis in small blood vessels, the subtle changes in the retinal arteries that are then hardened by hypertension known as hypertensive retinopathy. Most patients with hypertensive retinopathy have no visible symptoms at the beginning, but in some cases the general symptoms often associated with hypertensive retinopathy are those of headaches and eye pain. A vascularization of the retina as a result of hypertension if untreated, would become retinal hypertension, leading to a serious complication of blindness. The higher the blood pressure of people and the longer hypertension continues to cause greater damage. Keyword: Hipertension, hypertensive retinopathy, diagnose, management